Stability of Skyrmions on Curved Surfaces in the Presence of a Magnetic Field - Altbir-Drullinsky, D; Elias-Moreno, R; Carvalho-Santos, V (Elsevier, 2015)
We study the stability and energetics associated to skyrmions appearing as excitations on curved surfaces. Using a continuum model we show that the presence of cylindrically radial and azimuthal fields destabilize the skyrmions that appear in the absence of an external field. Weak fields generate fractional skyrmions while strong magnetic fields yield stable 2π-skyrmions, which have their widths diminished by the magnetic field strength. Under azimuthal fields vortex appears as stable state on the curved surface. © 2015 Elsevier B.V. All rights reserved.
Keywords: Heisenberg Model; Skyrmions; Vortices